The language stylisation in Czech translations of Pygmalion - Šafářová, Dita (2006)
The thesis describes specific features of drama with regards to translation as well as the influence of the ageing process on translation. It also qualifies and compares language variations in Czech and English. The main purpose of the paper is the analysis of four different Czech translations of the play Pygmalion, which are primarily evaluated from the stylistic point of view.